Reduced susceptibility and resistance to bedaquiline in clinical M. tuberculosis isolates - Peretokina, Irina V.; Krylova, Ludmila Yu; Antonova, Olga V.; Kholina, Margarita S.; Kulagina, Elena V.; Nosova, Elena Yu; Safonova, Svetlana G.; Borisov, Sergey E.; Zimenkov, Danila V. (The Journal of infection, 2020)
•Elevated bedaquiline MIC is found in clinical M. tuberculosis isolates.•MIC change is driven by mutations in mmpR (rv0678) and atpE genes.•AtpE substitutions G25S, D28G, D28N, E61D, A63P, and A63V were observed in vivo.•Substitutions in codon 63 of AtpE were likely associated with a higher bedaquiline MIC. Bedaquiline is an effective drug used to treat MDR and XDR tuberculosis, providing high cure rates in complex therapy. Mutations in the mmpR (rv0678) and atpE genes are associated with reduced susceptibility to bedaquiline and have been identified in both in vitro selected strains and clinical isolates. However, the phenotypic criteria used to detect bedaquiline resistance have yet to be established due to the collection of few clinical isolates from patients receiving bedaquiline-containing treatment regimens. One hundred eighty-two clinical isolates from 74 patients receiving bedaquiline and 163 isolates from 107 patients not exposed to bedaquiline were analysed. The bedaquiline MICs were tested using serial dilutions on 7H11 agar plates and the Bactec MGIT 960 system. The mmpR and atpE genes were sequenced by Sanger sequencing. The 7H11 agar method allowed for rapid discrimination between mutated and wild-type isolates and between exposed and non-exposed isolates. Seventy-three percent of bedaquiline-exposed isolates, as well as 91% of isolates with mutations, had an elevated bedaquiline MIC (≥ 0.12 mg/L on 7H11 media) compared to the reference isolates (89% had an MIC ≤ 0.03 mg/L). Previously reported in vitro-selected mutants (E61D and A63P) and novel AtpE substitutions (G25S and D28G) were observed in the clinical isolates. Substitutions in codon 63 of AtpE were likely associated with a higher bedaquiline MIC. Five new cases of pre-existing reduced susceptibility to bedaquiline, accompanied by mmpR mutations in most isolates, without a history of bedaquiline treatment were identified. Bedaquiline treatment leads to an elevated bedaquiline MIC and the acquisition of mmpR and atpE gene mutations in tuberculosis strains. The standardisation of bedaquiline phenotypic susceptibility testing is urgently needed based on observed discrepancies between our study and previous studies and differences in solid and liquid media MIC determinations.